Sectoral Diversification as Insurance against Economic Instability - Jan Kluge (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2015)
This paper examines the extent to which sectoral diversification can act as an insurancemechanism against fluctuations in regional gross value added growth rates. I apply portfoliotheory to the growth-instability properties of German districts. Furthermore, Idefine a comprehensive diversification measure and use Stochastic Frontier Analysis inorder to estimate whether diversification allows regions to achieve more efficientgrowth-instability combinations, i.e., greater stability at given levels of economicgrowth. The results confirm that diversification does generate such effects. Spatialinteractions do also play a role: The effects are less pronounced for regions whoseeconomic performance is mainly driven by the surrounding regions.
Keywords: L16; R11; R58; 330; Sectoral diversification; regional growth; economic instability